2019
DOI: 10.3389/fmicb.2019.00253
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of Sulfated Polysaccharides by Two Novel Kiritimatiellales Strains Isolated From Black Sea Sediment

Abstract: The marine environment contains a large diversity of sulfated polysaccharides and other glycopolymers. Saccharolytic microorganisms degrade these compounds through hydrolysis, which includes the hydrolysis of sulfate groups from sugars by sulfatases. Various marine bacteria of the Planctomycetes-Verrucomicrobia-Chlamydia (PVC) superphylum have exceptionally high numbers of sulfatase genes associated with the degradation of sulfated polysaccharides. However, thus far no sulfatase-rich mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 90 publications
(130 reference statements)
5
55
0
Order By: Relevance
“…However, it should be noted these gene clusters, that formed very long branches in the inferred phylogenetic tree, are in a badly resolved region of the tree also containing MBNT15, Acidobacteria, Actinobacteria and Verrucomicrobia (Supplementary Figure S1 for full description), which precludes a safe identification at present. Although, Kiritimatiellaeota phylum is not well described (Spring et al, 2016), strains from this group were recently identified as anaerobic degraders of sulfated polysaccharides compounds (Van Vliet et al, 2019). Such compounds are produced by marine algae and are generally abundant in marine waters (Helbert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted these gene clusters, that formed very long branches in the inferred phylogenetic tree, are in a badly resolved region of the tree also containing MBNT15, Acidobacteria, Actinobacteria and Verrucomicrobia (Supplementary Figure S1 for full description), which precludes a safe identification at present. Although, Kiritimatiellaeota phylum is not well described (Spring et al, 2016), strains from this group were recently identified as anaerobic degraders of sulfated polysaccharides compounds (Van Vliet et al, 2019). Such compounds are produced by marine algae and are generally abundant in marine waters (Helbert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kiritimatiellae are widespread and abundant in anoxic environments such as the intestinal tract of vertebrate animals [10,11] and marine or hypersaline sediments [9,12]. Our marine isolates, strains F1 T and F21 T , were found to represent a novel family-level Kiritimatiellae lineage [8] previously marked as ubiquitous yet uncultured (R76-B128) [13]. Currently, the only described species of the Kiritimatiellae class is Kiritimatiella glycovorans L21-Fru-AB T , a moderate halophile isolated from a hypersaline microbial mat [9].…”
Section: Introductionmentioning
confidence: 82%
“…K. glycovorans L21-Fru-AB T was ordered from the DSMZ (Braunschweig, Lower Saxony, Germany). Strains F1 T and F21 T were cultured in a basal anoxic bicarbonate-buffered marine medium described previously [8] containing 25 g L −1 NaCl for optimum salinity for growth, with 10 mM L-fucose as the substrate, unless mentioned otherwise. K. glycovorans was cultured in the same basal medium except for containing 60 g L −1 NaCl, with 5 mM D-glucose as the substrate.…”
Section: Strains Growth Conditions and Substratesmentioning
confidence: 99%
See 2 more Smart Citations